Association between Unmet Needs and Clinical Status in Patients with First Episode of Schizophrenia in Chile - Jorquera, Natalia; Alvarado, Rubén; Libuy, Nicolás; de Angel, Valeria (Frontiers in Psychiatry, 2015)
Background: Schizophrenia is a severe mental disorder involving needs in several matters that are often not covered. A need is defined as a gap between the ideal state and the current state of a patient about a specific topic. Aim: To describe needs in patients with first episode of schizophrenia at the start of treatment, and to describe associated clinical factors. Methods: Observational descriptive cross-sectional design. Patients were over fifteen years old, with first episode schizophrenia, and admitted to treatment in the public health system from six district in two cities of Chile, between 2005 and 2006. Sociodemographic data, clinical evaluations of current psychosis based on the PANSS, and the time of untreated psychosis were obtained. A clinical interview, was carried out followed by the Camberwell Assessment of Need. Results: 29 patients were evaluated, 79.3% male, mean age 21.9 years old. The areas with more needs reported were; psychotic symptoms with 65.5% of sample, 21.1% of which reported it unmet; and daytime activities, where 44.8% of patients reported a need, 61.54% of them as unmet. The percentage of unmet needs correlated with PANSS score (r= 0.55; p=0.003), and with time of positive symptoms prior to diagnosis (r= 0.416; p=0.03). Discussion: Needs assessment in schizophrenia is necessary. It may affect its clinical course, be relevant in its management and help monitor recovery. Defining the main needs in people with first episode schizophrenia and associated factors allows for a better design of treatment strategies in order to obtain better therapeutic results and recovery.